Los Juegos Didácticos Y Su Efecto En El Desarrollo Psicomotriz De Los Estudiantes De Primer Año De Educación Básica De La Unidad Educativa “Adolfo María Astudillo” Del Cantón Babahoyo. - Vega Jiménez, Verónica V. (2015)
This research work makes an analysis of the effect it has on the psychomotor development of the freshmen of basic education, the implementation of educational games used by teachers of the Education Unit "Adolfo Maria Astudillo," considering that educational games that are currently using does not improve dramatically the efficiency of the teaching-learning process with regard to the level of motor development awaited by children. Once it detected the problem we proceed to the development of the framework to properly substantiate the research variables, based on information collected from brochures, magazines, books, and Internet. Once the research methodology established appropriate tools for processing the same as that used for the quantitative and qualitative analysis of the variables investigated, proceeding to statistically analyze the data, being able to establish the relevant conclusions and recommendations were developed. Depending on what is revealed by the investigation proceeds to raise the Proposal for a Guide to Educational Games, the problem of the use of educational games in the psychomotor development through an educational guide Games.